Association of IL33, IL1RL1, IL1RAP Polymorphisms and Asthma in Chinese Han Children - Wu, Maolan; Zheng, Xiangrong; Huang, Juan; Hu, Xiaolei (Frontiers in Cell and Developmental Biology, 2021)
Background: Genome-wide association studies have identified interleukin 33 (IL33), interleukin 1 receptor-like 1 (IL1RL1), interleukin 1 receptor accessory protein (IL1RAP) as asthma susceptibility loci in Europeans. IL33, IL1RL1, and IL1RAP constitute a ligand-receptor complex. Objective: We analyzed associations of asthma susceptibility, eosinophilic airway inflammation, and response to inhaled corticosteroid (ICS) with single nucleotide polymorphisms (SNPs) of 3 genes encoding IL33, IL1RL1, and its coreceptor IL1RAP in Chinese Han nationality children. Methods: A total of 153 non-asthmatic children and 265 asthmatic children who visited the Xiangya Hospital between September 2015 and August 2019 were recruited for this study. Pulmonary function tests, peripheral blood eosinophil counts (PBEC), and fractional exhaled nitric oxide (FeNO) tests were performed before treatment, and 3 months after treatment. Each participant’s DNA was extracted from the peripheral blood, and a Mass ARRAY system was used to genotype the SNPs. Results: The T allele of rs4742170 in IL33 was associated with a risk of higher FeNO at baseline, and no improvement in FeNO and airway hyperresponsiveness was found after ICS treatment. The A allele of rs10208293 and C allele of rs13424006 in IL1RL1 both were associated with lower susceptibility to asthma and lower FeNO. The TT genotype of rs1420101 and AA genotype of rs4142132 in IL1RL1 were associated with a greater probability of improvement in PBEC after ICS treatment. Conclusion: IL33-IL1RL1-IL1RAP complex polymorphisms are associated with childhood asthma susceptibility, eosinophilic airway inflammation, and ICS response in Chinese Han children in Hunan. We speculate that IL33-IL1RL1-IL1RAP complex polymorphisms affect the development of asthma, airway inflammation, and subsequent ICS response in childhood.